"That was me": Reflektioner om Paul McCartney och relationen till den egna biografin - Kaijser, Lars (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2009)
This article focuses on how iconic figures like Paul McCartney relate to their own biographies. During the 1970’s, McCartney was reluctant in his relation to the Beatles. The eighties changed this. The nineties saw a McCartney who more openly made use of his own history. The Beatles became an iconic, visual, narrative and affective resource, which came to use in concerts as well as in record production. Central to McCartney’s use was also an ambition to get recognition for his contributions to the Beatles, largely dismissed since the murder of John Lennon, which credited Lennon as the creative genius of the band.